2020
DOI: 10.3389/fped.2020.00391
|View full text |Cite
|
Sign up to set email alerts
|

Increased Neutrophil Respiratory Burst Predicts the Risk of Coronary Artery Lesion in Kawasaki Disease

Abstract: Background: Kawasaki diseases (KD) is a febrile systemic vasculitis in infants associated with coronary aneurysm. The etiology of KD remains unclear. Human neutrophils have great capacity to cause tissue damage in inflammatory diseases via their inappropriate activation to release reactive oxygen species (ROS). Brain natriuretic peptide (BNP) is a substantial modulator of neutrophil activation to regulate ROS production. It is increasingly released from the myocardium in heart failure and myocardial inflammato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 27 publications
4
12
0
Order By: Relevance
“…Our meta-analysis integrates and unravels the consistency of several important individual studies and datasets that validate the transcriptome data at the protein level in COVID-19 patients [ 26 , 29 , 97 ]. In agreement with the recent observation that neutrophil hyperactivation plays a key role in the severity of COVID-19 [ 97 , 98 , 99 , 100 ], our study indicates that severe COVID-19 disease shares a common neutrophil activation signature with other different acute inflammatory conditions such as HLH [ 101 , 102 ], KD [ 103 , 104 , 105 ], and bacterial pneumonia [ 106 ]. Our data are in agreement with the dual role of neutrophils in providing essential antimicrobial functions, as well as in initiating tissue injury caused by immune dysregulation [ 107 , 108 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our meta-analysis integrates and unravels the consistency of several important individual studies and datasets that validate the transcriptome data at the protein level in COVID-19 patients [ 26 , 29 , 97 ]. In agreement with the recent observation that neutrophil hyperactivation plays a key role in the severity of COVID-19 [ 97 , 98 , 99 , 100 ], our study indicates that severe COVID-19 disease shares a common neutrophil activation signature with other different acute inflammatory conditions such as HLH [ 101 , 102 ], KD [ 103 , 104 , 105 ], and bacterial pneumonia [ 106 ]. Our data are in agreement with the dual role of neutrophils in providing essential antimicrobial functions, as well as in initiating tissue injury caused by immune dysregulation [ 107 , 108 ].…”
Section: Discussionsupporting
confidence: 92%
“…As we were able to demonstrate by the multi-omics association between leukocyte and plasma molecules, recently published flow cytometry and proteomic data indicate a systemic and integrated network of molecules associated with neutrophil growth, activation, and mobilization leading to neutrophil dysregulation in severe COVID-19 [ 98 , 99 ]. These results support the concept that the pathophysiology of HLH does not only involve T cell, NK cell and macrophage dysregulation, but also the hyperactivation of neutrophils, as this is also seen in patients with KD [ 103 , 104 , 105 ] and bacterial pneumonia [ 106 ].…”
Section: Discussionsupporting
confidence: 82%
“…Studys have showed that brain natriuretic peptide (BNP) play a signi cant role in the pathogenesis of KD [8], and predicts the risk of CAL in Kawasaki disease [9,10]. In this study, we detected the level of BNP in IVIG + IVMP group with CAL and without CAL.…”
Section: Introductionmentioning
confidence: 67%
“…For example, neutrophils during phagocytosis undergo a process termed as the “respiratory burst” that involves the activation of enzymes such as NADPH oxidase, leading to the production of superoxide. ROS, although essential for the normal functioning of immune cells, have a detrimental effects on DNA integrity and chromatin organization (El-Benna et al, 2016; Hu et al, 2020; Salinas et al, 2020). Various inflammatory processes that are associated with increased ROS generation have been linked to genetic damage.…”
Section: Discussionmentioning
confidence: 99%